2019
DOI: 10.1142/s2010135x19500346
|View full text |Cite
|
Sign up to set email alerts
|

Low dielectric constant and signature of ferroelectric nature in transition metal (Co, Ni, Cu)-doped Mg0.5Zn0.5Al2O4 aluminates

Abstract: This paper throws light on the preparation of transition metal-doped Mg[Formula: see text]Zn[Formula: see text]Al2O4 ([Formula: see text], 0.05 and [Formula: see text], Ni, Cu) aluminates via solid-state reaction route. The X-ray diffraction characterization analysis confirmed that all the samples have crystallized into the psuedocubic phase having space group Fd3[Formula: see text] and were single phased. The incorporation of transition metals viz. Co[Formula: see text], Ni[Formula: see text], Cu[Formula: see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…According to the micrographs, the crystals are well separated from one another and there isn't a definite grain boundary. The FESEM images show that the agglomeration phenomena predominates [22][23][24]. ImageJ software was used to calculate the average particle size, which came out to be 1.13 μm.…”
Section: Compositional and Microstructural Studiesmentioning
confidence: 99%
“…According to the micrographs, the crystals are well separated from one another and there isn't a definite grain boundary. The FESEM images show that the agglomeration phenomena predominates [22][23][24]. ImageJ software was used to calculate the average particle size, which came out to be 1.13 μm.…”
Section: Compositional and Microstructural Studiesmentioning
confidence: 99%
“…In the composite system, the inter-diffusion of phases reduce bandgap value and in the response of which the movement of electrons becomes easier. 41,42 The lower value of " 0 of (0.75) La 0:9 Na 0:1 CrO 3 þ (0.25) Ni 0:5 Cu 0:5 Fe 2 O 4 compared to (0.5) La 0:9 Na 0:1 CrO 3 þ (0.5) Ni 0:5 Cu 0:5 Fe 2 O 4 can be due to lesser crystallinity and nonuniform distribution of NCFO phase in the LNCO matrix as revealed from the FESEM micrographs. The mechanism through which the polarization takes place is similar to that in conduction process which highly relies on the synthesis method, chemical composition, crystallite size and cation distribution.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…Furthermore, the ac conductivity tends to attain maximum value with increasing frequency as the immigration of electrons is increased. [39][40][41][42][43][44][45]49 The ac conductivity can be seen increasing with increase in frequency and becomes independent of frequency after a certain value. The lower part of frequency will give direct current conductivity ð dc Þ.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…At lower frequencies the electron hopping between Al 2+ to Al 3+ ions cause the polarization. The different polarization mechanisms such as charge displacement (electronic and ionic), orientation and interfacial polarization contribute to maximum value of dielectric constant at lower frequency whereas, at higher frequency, polarization starts ceasing and after a certain frequency the electron hopping (Al 2+ -Al 3+ ) cannot follow the rapid variation of external applied field [4,5]. In magnesium aluminates, MgO behaves as a p-type semiconducting material and Al2O3 as a dielectric material.…”
Section: Introductionmentioning
confidence: 99%
“…Plot of dielectric loss with frequency for MgAl2O4 sample.5. Temperature dependent dielectric characteristicsFigure(5) depicts the change in value of dielectric constant (ɛ') as a function of temperature at frequencies, 100Hz, 1000Hz, 10000Hz and 100000Hz for MgAl2O4 compound. From the figure it is observed that at higher temperature, the drift mobility of charge carriers and their hopping rate increases by thermal energy, which causes an increase in polarization but at lower temperatures, thermal energy is not enough to increase the hopping rate of charge carriers and…”
mentioning
confidence: 99%